Clinical experience of comprehensive treatment on the balance function of Parkinson's disease. Issue 19 (May 2020) - Li, Haitao; Liang, Siquan; Yu, Yang; Wang, Yue; Cheng, Yuanyuan; Yang, Hechao; Tong, Xiaoguang
Abstract : Abstract: To investigate the effect of multi-disciplinary teamwork on balance performance of Parkinson's disease (PD). Sixteen primary Parkinson's disease patients (8 male, 8 female) treated with bilateral subthalamic nucleus deep brain stimulation (STN-DBS) were included in the study. The median age of patients was 60.5 years; all patients were in the Hoehn&Yahr (H&Y) 3 stage; the median PD duration of the disease was 9 years. For each patient, multi-disciplinary teamwork treatment including DBS, medication, physical therapy and psychotherapy proceeded. levodopa equivalent daily dose (LEDD, mg/day), life quality (PDQ-39), Motor disability (MDS-UPDRSIII) and balance performance (MDS-UPDRS 3.12, Berg Balance Scale BBS, Limits of Stability LoS) were assessed in different time and status respectively: preoperation (Med-off, Med-on), postoperation (Stim-Off/Med-Off, Stim-On/Med-Off, Stim-On/Med-On), 6 months postoperation (Stim-On/ Med-Off, Stim-On/Med-On) and 12 months postoperation (Stim-On/Med-Off, Stim-On/Med-On). The LEDD, life quality (PDQ-39) continued to improve during the follow-up, statistical difference were found in both 6 months postoperation and 12 months postoperation compared with preoperation. The Motor disability (MDS-UPDRSIII), balance performance (MDS-UPDRS 3.12, BBS) and the LoS (target acquisition percentage, trunk swing angle standard deviation, time) showed significant improvement in Stim-On/med-Off 6 months postoperation and 12 months postoperation separately compared with Med-Off preoperation. Multi-disciplinary teamwork for PD patients with STN-DBS could improve balance performance.